A facile, stereoselective, one-pot synthesis of resveratrol derivatives - Birar, Vishal C (Chem Cent J, 2015)
BACKGROUND: Compounds based on trans-1,2-diphenylethene are the subject of intense interest both for their optical properties and as potential leads for drug discovery, as a consequence of their anticancer, anti-inflammatory and antioxidant properties. Perhaps the best known of these is trans-3,5,4′-trihydroxystilbene (resveratrol), that has been identified as a promising lead in the search for anti-ageing therapeutics. RESULTS: We report here a new, convenient, one-pot stereo-selective synthesis of resveratrol and other trans-stilbene derivatives. A wide range of known and novel “Resveralogues” were synthesised by using this simple protocol, including examples with electron donating and electron withdrawing substituents, in uniformly high yield. The structures of all compounds were confirmed by standard methods including (1)H and (13)C NMR, IR and High Resolution Mass spectroscopy. CONCLUSIONS: We have established a simple and convenient protocol for resveralogue synthesis. It is readily scalable, and sufficiently robust and simple for ready use in automated synthesis or for library development of resveralogues. This supersedes previously reported synthetic methods that required inert conditions, extensive purification and/or costly reagents. [Figure: see text]